2014
DOI: 10.1016/j.bjhh.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclosporine on the occurrence of nephrotoxicity after allogeneic hematopoietic stem cell transplantation: a systematic review

Abstract: Cyclosporine, a drug used in immunosuppression protocols for hematopoietic stem cell transplantation that has a narrow therapeutic index, may cause various adverse reactions, including nephrotoxicity. This has a direct clinical impact on the patient. This study aims to summarize available evidence in the scientific literature on the use of cyclosporine in respect to its risk factor for the development of nephrotoxicity in patients submitted to hematopoietic stem cell transplantation. A systematic review was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
2
12
1
6
Order By: Relevance
“…Previous studies reported that the incidence of AKD during transplantation ranged from 17% and 73%. Even this condition is as high as 90% in some studies (11,12). In our study, AKD developed in 32.5% of patients.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Previous studies reported that the incidence of AKD during transplantation ranged from 17% and 73%. Even this condition is as high as 90% in some studies (11,12). In our study, AKD developed in 32.5% of patients.…”
Section: Discussioncontrasting
confidence: 40%
“…Saddani et al showed that amphotericin B use is an independent risk factor for AKD in HSCT patients (24). It is well know that cyclosporine and amphotericin B may lead to acute tubular necrosis (11). In this study, amphotericin B was applied in 24.7% of patients and amphotericin B use was higher in patients developing AKD.…”
Section: Discussionmentioning
confidence: 85%
“…Insuficiência renal ou lesão renal aguda foi definida como o aumento da creatinina ≥ 2 vezes o valor basal (70,73) .…”
Section: Sobrevida Global (Sg) Representa O Tempo De Vida Do Dia Da unclassified
“…Possíveis explicações para esta taxa reduzida (73,85,86) incluem aspectos identificados neste estudo tais como: a maioria dos pacientes apresentaram compatibilidade HLA, enxerto oriundo de doadores aparentados, associação de dois imunossupressores (CSP e MTX; CSP e MMF) e regime de condicionamento NMA.…”
Section: Discussão Discussãounclassified
See 1 more Smart Citation